Atypical mycobacterial cervical lymphadenopathy in a 2-year-old girl - Anna Fedorowicz; Michal Jerzy Pasierbek; Wojciech Korlacki (Termedia Publishing House, 2023)
Lymphadenopathy is a common clinical condition in the paediatric population. In 50% of cases it occurs in otherwise healthy children, and in 75% it presents as a localized form. Lymphadenopathy lasting more than 3 months is defined as chronic. Common conditions causing lymph node enlargement include infections, malignancies, and autoimmune disorders. Mycobacteria causing infectious lymphadenopathy are divided into tuberculous and non-tuberculous mycobacteria (NTM). Diagnosing mycobacterial disease is complicated, and definitive surgery is the best treatment option for NTM cervicofacial lymphadenitis. We present a case of a 2-year-old girl with chronic cervical lymphadenopathy, eventually diagnosed as NTM infection. The diagnostic and therapeutic process was complicated, demanding an interdisciplinary approach and several surgical procedures. The treatment was supported by negative pressure therapy.